Entrepreneurship through Market-Linked Extension: Role of Institutional Innovations - Cudney, Patrick; Lyons, Thomas S; Moore, Erin; Sivakumar, Sethuraman; Alex, Jiju P; Gummagolmath, K C; Madan, Sunil; S, Shalendra (Journal of Agricultural Extension Management, 2020)
In spite of tremendous agricultural growth, the challenge is to grow more food to feed the growing population. Innovations have the potential to offer solutions as per local needs and capacities of farming communities; though, technical innovations have to be pursued in association with institutional innovations for their inter-dependence. This paper presents some of the institutional innovations adopted by different organisations to enhance the reach of technology and services to end-users. Some of these models have their focus on innovator/ innovation while others on multiplication and distribution of technology. The focus of innovator-based models is mainly on the development of innovations while models with focus on multiplication and distribution aim at taking already developed technology to the end-users. Institutional arrangements to facilitate ScientistFarmer interface can also help farmers collaborate to learn from each other. An analysis of the models covered under the study emphasizes on the importance of involving extension machinery in any institutional model adopted by an organisation, private or public, for both developing innovations and taking them to the end-users.